Biochemical Evaluation of Jihua Hemostatic Suppository in Hemorrhagic Internal Hemorrhoids: Modulation of Xpo1, VEGF, and Collagen I/III Expression and Inflammatory Biomarkers: Biochemical Modulation by Jihua Suppository in Hemorrhagic Hemorrhoids - Wang, Chao; Kang, Yajun; Wang, Ye; Liu, Yujie; Shi, Mengli; Liu, Xiaoming; Jiao, Hao (Journal of Medical Biochemistry, 2025)
Background: Hemorrhagic internal hemorrhoids involve abnormal vascular remodeling, inflammatory activation, and extracellular matrix dysregulation. Exportin-1 (Xpo1), vascular endothelial growth factor (VEGF), and collagen types I and III are key biochemical markers associated with these processes. This study aimed to evaluate the therapeutic efficacy of Jihua Hemostatic Suppository compared with Gangtai Suppository and to investigate their differential effects on biochemical and inflammatory parameters in patients with hemorrhagic internal hemorrhoids.Methods: A total of 98 patients diagnosed with hemorrhagic internal hemorrhoids were enrolled between January 2024 and January 2025 and randomly divided into two groups (n = 49 each) using the envelope randomization method. The Jihua group received Jihua Hemostatic Suppository, whereas the control group received Gangtai Suppository for two weeks. Serum levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) were determined by ELISA. Xpo1 levels were measured by ELISA, VEGF by chemiluminescence assay, and collagen types I and III by the hydroxyproline method. Clinical efficacy, traditional Chinese medicine (TCM) syndrome scores, and adverse reactions were also recorded.Results: The total effective rate in the Jihua group (93.88%) was significantly higher than that in the Gangtai group (77.55%) (χ² = 5.968, P = 0.015). After treatment, the Jihua group showed markedly lower serum IL-6 (70.50 ± 5.82 ng/mL), CRP (23.06 ± 2.71 mg/L), and TNF-α (60.81 ± 5.72 ng/mL) levels compared with the Gangtai group (P < 0.001). Biochemically, Xpo1, VEGF, collagen I, and collagen III concentrations were significantly reduced in the Jihua group (12.31 ± 1.35 ng/mL, 389.64 ± 34.32 pg/mL, 154.39 ± 15.19 pg/L, and 36.13 ± 3.06 μg/L, respectively) compared with the Gangtai group (P < 0.05). The incidence of adverse reactions was lower with Jihua suppository (4.08%) than with Gangtai suppository (20.41%) (χ² = 4.242, P = 0.039).Conclusion: Jihua Hemostatic Suppository exerts superior therapeutic and biochemical effects in hemorrhagic internal hemorrhoids compared with Gangtai Suppository. Its efficacy is likely mediated by suppression of the Xpo1/NF-κB inflammatory axis, inhibition of VEGF-driven angiogenesis, and normalization of collagen I/III-dependent extracellular matrix remodeling. These findings highlight the value of integrating biochemical biomarkers into clinical assessment of hemorrhoidal disease and suggest Xpo1, VEGF, and collagen I/III as potential molecular indicators of treatment efficacy.
Keywords: Jihua Hemostatic Suppository; Gangtai Suppository; Hemorrhagic Internal Hemorrhoids; Exportin-1 (Xpo1); Vascular Endothelial Growth Factor (VEGF); Collagen I/III; Inflammatory Biomarkers; Biochemical Modulation